Segmental Colitis Complicating Diverticular Disease - Guido Ma Van Rosendaal; Melvin A Andersen (Canadian Journal of Gastroenterology)
Two cases of idiopathic colitis affecting the sigmoid colon in elderly patients with underlying diverticulosis are presented. Segmental resection has permitted close review of the histopathology in this syndrome which demonstrates considerable similarity to changes seen in idiopathic ulcerative colitis. The reported experience with this syndrome and its clinical features are reviewed.